Detection of homozygous and hemizygous complete or partial exon deletions by whole-exome sequencing. - Bigio, Benedetta; Seeleuthner, Yoann; Kerner, Gaspard; Migaud, Mélanie; Rosain, Jérémie; Boisson, Bertrand; Nasca, Carla; Puel, Anne; Bustamante, Jacinta; Casanova, Jean-Laurent; Abel, Laurent; Cobat, Aurelie (NAR Genom Bioinform, 2021)
The detection of copy number variations (CNVs) in whole-exome sequencing (WES) data is important, as CNVs may underlie a number of human genetic disorders. The recently developed HMZDelFinder algorithm can detect rare homozygous and hemizygous (HMZ) deletions in WES data more effectively than other widely used tools. Here, we present HMZDelFinder_opt, an approach that outperforms HMZDelFinder for the detection of HMZ deletions, including partial exon deletions in particular, in WES data from laboratory patient collections that were generated over time in different experimental conditions. We show that using an optimized reference control set of WES data, based on a PCA-derived Euclidean distance for coverage, strongly improves the detection of HMZ complete exon deletions both in real patients carrying validated disease-causing deletions and in simulated data. Furthermore, we develop a sliding window approach enabling HMZDelFinder_opt to identify HMZ partial deletions of exons that are undiscovered by HMZDelFinder. HMZDelFinder_opt is a timely and powerful approach for detecting HMZ deletions, particularly partial exon deletions, in WES data from inherently heterogeneous laboratory patient collections.

Inhibition of HECT E3 ligases as potential therapy for COVID-19. - Novelli, Giuseppe; Liu, Jing; Biancolella, Michela; Alonzi, Tonino; Novelli, Antonio; Patten, J J; Cocciadiferro, Dario; Agolini, Emanuele; Colona, Vito Luigi; Rizzacasa, Barbara; Giannini, Rosalinda; Bigio, Benedetta; et al. (Cell Death Dis, 2021)
SARS-CoV-2 is responsible for the ongoing world-wide pandemic which has already taken more than two million lives. Effective treatments are urgently needed. The enzymatic activity of the HECT-E3 ligase family members has been implicated in the cell egression phase of deadly RNA viruses such as Ebola through direct interaction of its VP40 Protein. Here we report that HECT-E3 ligase family members such as NEDD4 and WWP1 interact with and ubiquitylate the SARS-CoV-2 Spike protein. Furthermore, we find that HECT family members are overexpressed in primary samples derived from COVID-19 infected patients and COVID-19 mouse models. Importantly, rare germline activating variants in the NEDD4 and WWP1 genes are associated with severe COVID-19 cases. Critically, I3C, a natural NEDD4 and WWP1 inhibitor from Brassicaceae, displays potent antiviral effects and inhibits viral egression. In conclusion, we identify the HECT family members of E3 ligases as likely novel biomarkers for COVID-19, as well as new potential targets of therapeutic strategy easily testable in clinical trials in view of the established well-tolerated nature of the Brassicaceae natural compounds.
Keywords: Adult; Aged; Animals; Antiviral Agents; Chlorocebus aethiops; COVID-19; Endosomal Sorting Complexes Required for Transport; Female; Humans; Indoles; Male; Mice; Mice, Inbred BALB C; Middle Aged; Nedd4 Ubiquitin Protein Ligases; SARS-CoV-2; Spike Glycoprotein, Coronavirus; Ubiquitin-Protein Ligases; Ubiquitination; Vero Cells

Autoantibodies against type I IFNs in patients with life-threatening COVID-19. - Bastard, Paul; Rosen, Lindsey B; Zhang, Qian; Michailidis, Eleftherios; Hoffmann, Hans-Heinrich; Zhang, Yu; Dorgham, Karim; Philippot, Quentin; Rosain, Jérémie; Béziat, Vivien; Manry, Jeremy; Shaw, Elana; et al. (Science, 2020)
Interindividual clinical variability in the course of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection is vast. We report that at least 101 of 987 patients with life-threatening coronavirus disease 2019 (COVID-19) pneumonia had neutralizing immunoglobulin G (IgG) autoantibodies (auto-Abs) against interferon-ω (IFN-ω) (13 patients), against the 13 types of IFN-α (36), or against both (52) at the onset of critical disease; a few also had auto-Abs against the other three type I IFNs. The auto-Abs neutralize the ability of the corresponding type I IFNs to block SARS-CoV-2 infection in vitro. These auto-Abs were not found in 663 individuals with asymptomatic or mild SARS-CoV-2 infection and were present in only 4 of 1227 healthy individuals. Patients with auto-Abs were aged 25 to 87 years and 95 of the 101 were men. A B cell autoimmune phenocopy of inborn errors of type I IFN immunity accounts for life-threatening COVID-19 pneumonia in at least 2.6% of women and 12.5% of men.
Keywords: Adult; Aged; Aged, 80 and over; Antibodies, Neutralizing; Asymptomatic Infections; Autoantibodies; Betacoronavirus; Case-Control Studies; Coronavirus Infections; COVID-19; Critical Illness; Female; Humans; Immunoglobulin G; Interferon alpha-2; Interferon Type I; Male; Middle Aged; Pandemics; Pneumonia, Viral; SARS-CoV-2

A genome-wide case-only test for the detection of digenic inheritance in human exomes. - Kerner, Gaspard; Bouaziz, Matthieu; Cobat, Aurelie; Bigio, Benedetta; Timberlake, Andrew T; Bustamante, Jacinta; Lifton, Richard P; Casanova, Jean-Laurent; Abel, Laurent (Proc Natl Acad Sci U S A, 2020)
Whole-exome sequencing (WES) has facilitated the discovery of genetic lesions underlying monogenic disorders. Incomplete penetrance and variable expressivity suggest a contribution of additional genetic lesions to clinical manifestations and outcome. Some monogenic disorders may therefore actually be digenic. However, only a few digenic disorders have been reported, all discovered by candidate gene approaches applied to at least one locus. We propose here a two-locus genome-wide test for detecting digenic inheritance in WES data. This approach uses the gene as the unit of analysis and tests all pairs of genes to detect pairwise gene × gene interactions underlying disease. It is a case-only method, which has several advantages over classic case-control tests, in particular by avoiding recruitment of controls. Our simulation studies based on real WES data identified two major sources of type I error inflation in this case-only test: linkage disequilibrium and population stratification. Both were corrected by specific procedures. Moreover, our case-only approach is more powerful than the corresponding case-control test for detecting digenic interactions in various population stratification scenarios. Finally, we confirmed the potential of our unbiased, genome-wide approach by successfully identifying a previously reported digenic lesion in patients with craniosynostosis. Our case-only test is a powerful and timely tool for detecting digenic inheritance in WES data from patients.
Keywords: Craniosynostoses; Epistasis, Genetic; Exome; Genetic Linkage; Genetic Variation; Genome-Wide Association Study; High-Throughput Nucleotide Sequencing; Humans; Models, Genetic; Multifactorial Inheritance; Whole Exome Sequencing

Inborn errors of type I IFN immunity in patients with life-threatening COVID-19. - Zhang, Qian; Bastard, Paul; Liu, Zhiyong; Le Pen, Jérémie; Moncada-Velez, Marcela; Chen, Jie; Ogishi, Masato; Sabli, Ira K D; Hodeib, Stephanie; Korol, Cecilia; Rosain, Jérémie; Bilguvar, Kaya; et al. (Science, 2020)
Clinical outcome upon infection with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) ranges from silent infection to lethal coronavirus disease 2019 (COVID-19). We have found an enrichment in rare variants predicted to be loss-of-function (LOF) at the 13 human loci known to govern Toll-like receptor 3 (TLR3)- and interferon regulatory factor 7 (IRF7)-dependent type I interferon (IFN) immunity to influenza virus in 659 patients with life-threatening COVID-19 pneumonia relative to 534 subjects with asymptomatic or benign infection. By testing these and other rare variants at these 13 loci, we experimentally defined LOF variants underlying autosomal-recessive or autosomal-dominant deficiencies in 23 patients (3.5%) 17 to 77 years of age. We show that human fibroblasts with mutations affecting this circuit are vulnerable to SARS-CoV-2. Inborn errors of TLR3- and IRF7-dependent type I IFN immunity can underlie life-threatening COVID-19 pneumonia in patients with no prior severe infection.
Keywords: Adolescent; Adult; Aged; Aged, 80 and over; Alleles; Asymptomatic Infections; Betacoronavirus; Child; Child, Preschool; Coronavirus Infections; COVID-19; Female; Genetic Loci; Genetic Predisposition to Disease; Humans; Infant; Interferon Regulatory Factor-7; Interferon Type I; Loss of Function Mutation; Male; Middle Aged; Pandemics; Pneumonia, Viral; Receptor, Interferon alpha-beta; SARS-CoV-2; Toll-Like Receptor 3; Young Adult